Influence of fluorine plasma treatment of TiO2 films on the behavior of dye solar cells employing the Co(II)/(III) redox couple - Konstantakou, M.; Stergiopoulos, T.; V. Likodimos; Vougioukalakis, G C; Sygellou, L.; A. G. Kontos; Tserepi, A.; P. Falaras (Journal of Physical Chemistry C, 2014)
Fluorine plasma treatment was investigated as an appropriate means for the surface modification of TiO2 thin film electrodes and the optimization of their performance as photoanodes in dye solar cells (DSCs) employing the Co(II)/(III) redox shuttle and the organic D35 sensitizer. Detailed surface and structural characterization of the titania films by contact angle measurements, atomic force microscopy, profilometry, and Raman and UV-vis spectroscopy showed that high density SF6 plasma provoked severe film densification and thus an increase of the nanoparticles packing density, leaving intact the crystallinity, particle size, and optical bandgap. Surface fluorination of the TiO2 films was also identified by X-ray photoelectron spectroscopy. The combination of the above effects resulted in the enhancement of both photocurrent and power conversion efficiency of the corresponding DSCs at moderate plasma treatment durations, while the photovoltage decreased continuously as a function of the fluorine processing time. Electrochemical impedance spectroscopy analysis revealed a marked increase of the density and distribution of trap states due to fluorine induced surface states along with a systematic downward shift of the TiO2 conduction band, probably attributed to the electrostatic coupling of intercalated Li + cations with the polar Ti-F species at the TiO2 surface, in agreement with the Voc drop. In contrast, enhanced electron injection was inferred to underlie the observed Jsc and DSC performance improvements, as surface fluorination and the concomitant film densification slightly increased electron transport while hardly affecting dye loading capacity, light harvesting efficiency, and recombination kinetics, except for the case of prolonged plasma treatment. Effective control of the detrimental side effects of fluorine species can render this kind of plasma treatment a powerful method to tune the surface and electrical properties of TiO2 films and optimize the behavior and performance of the resulting DSC devices. © 2014 American Chemical Society.
cited By 13